2022
DOI: 10.3390/ijms231911607
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of the PD-1/PD-L1/PD-L2 Pathway in Patients Suffering from Endometriosis

Abstract: The interaction between dendritic cells (DCs) and T cells mediated by the programmed cell death 1 (PD-1)/programmed cell death ligand 1 (PD-L1)/programmed cell death ligand 2 (PD-L2) pathway is the most important point in regulating immunological tolerance and autoimmunity. Disturbances in the quantity, maturity, and activity of DCs may be involved in the implantation and growth of endometrial tissue outside the uterus in endometriosis (EMS). However, little is known about the role of the immune checkpoint pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Women with EMS are noted to have altered peripheral and peritoneal cells activity, including the reduced cytotoxicity of the NK cells or decreased T cell reactivity, which lead to the failure in removing fragments of the endometrium from the peritoneal cavity and induces excessive local inflammation [ 25 ]. In our previous research study, we observed a higher frequency of mDCs and pDCs with PD-L1 and PD-L2 expression in the PF of patients with EMS [ 8 ]. In the current study, we explored the expression of Gal-9 on the mDCs and pDCs in both the systemic and local peritoneal environment of EMS patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Women with EMS are noted to have altered peripheral and peritoneal cells activity, including the reduced cytotoxicity of the NK cells or decreased T cell reactivity, which lead to the failure in removing fragments of the endometrium from the peritoneal cavity and induces excessive local inflammation [ 25 ]. In our previous research study, we observed a higher frequency of mDCs and pDCs with PD-L1 and PD-L2 expression in the PF of patients with EMS [ 8 ]. In the current study, we explored the expression of Gal-9 on the mDCs and pDCs in both the systemic and local peritoneal environment of EMS patients.…”
Section: Discussionmentioning
confidence: 99%
“…The key features of EMS include the presence of an increased PF volume with chronic peritoneal inflammation, disturbances of immune cells, secreted cytokines, and growth factors, which are critical for the survival of ectopic endometrial implants [ 42 ]. In our previous research study, we showed an accumulation of mDCs, mDCs, and pDCs with PD-L1 and PD-L2 expression, in the PF of EMS patients [ 8 ]. In the present study, we observed the accumulation of mDCs-Gal-9 + , pDCs-Gal-9 + , and a soluble form of Gal-9 and TIM-3 in the PF of EMS patients in comparison to the periphery ( Figure 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations